The effect of prenatal fumonisin B exposure on bone innervation in newborn Wistar rats - Tomaszewska Ewa; Dobrowolski Piotr; Dajnowska Aleksandra; Arbatowska Liwia; Puzio Iwona; Rudyk Halyna; Brezvyn Oksana; Kotsyumbas Ihor; Donaldson Janine; Śliwa Jadwiga; Arciszewski Marcin B.; Muszyński Siemowit (Journal of Veterinary Research)
This study explored the effects of prenatal exposure to fumonisins B (FB) on bone innervation in newborn Wistar rats.